Differences in Cardiovascular Disease Risk Factor Management in Primary Care by Sex of Physician and Patient - Tabenkin, Hava (American Academy of Family Physicians, 2010)
PURPOSE The purpose of this study was to evaluate differences in the management of cardiovascular disease (CVD) risk factors based upon the sex of the patient and physician and their interaction in primary care practice. METHODS We evaluated CVD risk factor management in 4,195 patients cared for by 39 male and 16 female primary care physicians in 30 practices in southeastern New England. RESULTS Many of the sex-based differences in CVD risk factor management on crude analysis are lost once adjusted for confounding factors found at the level of the patient, physician, and practice. In multilevel adjusted analyses, styles of CVD risk factor management differed by the sex of the physician, with more female physicians documenting diet and weight loss counseling for hypertension (odds ratio [OR] = 2.22; 95% confidence interval [CI], 1.12–4.40) and obesity (OR = 2.14; 95% CI, 1.30–3.51) and more physical activity counseling for obesity (OR = 2.03; 95% CI, 1.30–3.18) and diabetes (OR = 6.55; 95% CI, 2.01–21.33). Diabetes management differed by the sex of the patient, with fewer women receiving glucose-lowering medications (OR = 0.49; 95% CI, 0.25–0.94), angiotensin-converting enzyme inhibitor therapy (OR = 0.39; 95% CI, 0.22–0.72), and aspirin prophylaxis (OR = 0.30; 95% CI, 0.15–0.58). CONCLUSION Quality of care as measured by patients meeting CVD risk factors treatment goals was similar regardless of the sex of the patient or physician. Selected differences were found in the style of CVD risk factor management by sex of physician and patient.